Intraday trading patterns in Bitcoin: does the war in Ukraine matter? - Miłobędzki, Paweł (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: So far, nothing has been known about the impact of the war in Ukraine on the dynamics of cryptocurrency markets, in particular on the intraday trading patterns in Bitcoin, nowadays the largest market capitalization and trading volume cryptocurrency. Aim: Use the data from the period January–April 2022 exhibiting over 1.5 million trades at Bitstamp, one out of four largest in trading volume Bitcoin markets, to identify and compare the day of the week and the hour of the day effects in the rate of return, bid-ask spread and trading volume at times preceding and following the war outbreak. Results: The analysis based on the regression including dummy variables showed that the bid-ask spread and trading volume exhibited both the day of the week and the hour of the day effects. The same applied to the rate of return — but only incidentally. The effects differed in the magnitude across the peace and war periods being mostly smaller in the latter one due to increased risk faced by market participants who, as reflected in the number of trades and trading volume, lowered their activity. Since Bitcoin at Bitstamp is traded 24 hours a day and 7 days a week and incoming information is continuously impounded into its prices, the intraday trading patterns are different from those at the mature and emerging stock markets. The wider spreads and larger trading volumes were found present close to open of the major stock markets (NYSE, NASDAQ, London, Frankfurt, Tokyo).